Hubungan Antara Body Shaming Dan Kecemasan Sosial Pada Siswa SMA Harapan 3 - Mery Christine Lumban Gaol; Sabrini Mentari Rezeki; Siti Rahma Aura; Ade Intan Felicia Sianturi; Achmad Irvan Dwi Putra; Lusinta Rehna Ginting; Nurvica Sary (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between body shaming and social anxiety in students of SMA Harapan 3. This study uses a quantitative method with a correlational design. For data collection, the disproportionate stratified random sampling technique was used. This study used a population of 140 students with a sample of 100 respondents. The research instrument used includes two scales, namely the anxiety scale with 31 statements and a reliability of 0.753 and the body shaming scale with 24 statements and a reliability of 0.757. The results of the study found that the higher the body shaming, the higher the anxiety experienced by students. With a product moment value of 0.778 with a significance value (p) of 0.000 (p < 0.05). This indicates a positive relationship between the two variables with a significant level of relationship which is included in the fairly strong category.